Clinical and metabolic characteristics of endometrial lesions in polycystic ovary syndrome at reproductive age - Xiaozhu Zhong⋅; Yang Li⋅; Weiying Liang; Qiyue Hu; Anqi Zeng; Miao Ding; Dongmei Chen; Meiqing Xie (BMC, 2023)
Abstract Background We aimed to explore the clinical and metabolic characteristics in polycystic ovary syndrome (PCOS) patients with different endometrial lesions. Methods 234 PCOS patients who underwent hysteroscopy and endometrial biopsy were categorized into four groups: (1) normal endometrium (control group, n = 98), (2) endometrial polyp (EP group, n = 92), (3) endometrial hyperplasia (EH group, n = 33), (4) endometrial cancer (EC group, n = 11). Serum sex hormone levels, 75 g oral glucose tolerance test, insulin release test, fasting plasma lipid, complete blood count and coagulation parameters were measured and analyzed. Results Body mass index and triglyceride level of the EH group were higher while average menstrual cycle length was longer in comparison with the control and EP group. Sex hormone-binding globulin (SHBG) and high density lipoprotein were lower in the EH group than that in the control group. 36% of the patients in the EH group suggested obesity, higher than the other three groups. Using multivariant regression analysis, patients with free androgen index > 5 had higher risk of EH (OR 5.70; 95% CI 1.05-31.01), while metformin appeared to be a protective factor for EH (OR 0.12; 95% CI 0.02-0.80). Metformin and hormones (oral contraceptives or progestogen) were shown to be protective factors for EP (OR 0.09; 95% CI 0.02-0.42; OR 0.10; 95% CI 0.02-0.56). Hormones therapy appeared to be a protective factor for EC (OR 0.05; 95% CI 0.01-0.39). Conclusion Obesity, prolonged menstrual cycle, decreased SHBG, and dyslipidemia are risk factors for EH in patients with PCOS. Oral contraceptives, progestogen and metformin are recommended for prevention and treatment of endometrial lesions in PCOS patients.